Dyes based on the 6, 7‐dichloro‐5, 8‐quinolinedione skeleton as new type II photoinitiators for radical polymerisation. (13th March 2014) - Orzeł, Agnieszka; Podsiadły, Radosław; Podemska, Karolina; Strzelczyk, Rafał; Kolińska, Jolanta; Sokołowska, Jolanta
<x xml:space="preserve">Abstract</x> Several dyes based on the 6, 7‐dichloro‐5, 8‐quinolinedione skeleton have been synthesised and characterised by proton nuclear magnetic resonance spectroscopy and electron ionisation mass spectrometry. The spectroscopic and electrochemical properties of these dyes were investigated. Photoredox pairs consisting of the synthesised dyes and commercially available hydrogen donors (2‐mercaptobenzoxazole, 2‐mercaptobenzothiazole, 2‐mercaptobenzimidazole, and 2, 5‐dimercapto‐1, 3, 4‐thiadiazole) were tested for use as effective initiator systems for radical polymerisation of trimethylolpropane triacrylate with visible light. The efficiencies of these initiator systems are discussed in terms of the free energy change for the electron transfer process from the dye to the hydrogen donor.